Study of effect of argument driven inquiry model and mathematical literacy on student mathematical communication - Ambarwati, Riyama; Supriadi, Nanang; Noviana, Dewi; Putra, Rizki Wahyu Yunian; Mujib, Mujib; Andriani, Siska (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: Mathematical communication skills are an important aspect of mathematics learning that allows students to explore and consolidate their mathematical thinking clearly and precisely.Aim: This study aims to analyze the effect of Argument Driven Inquiry learning model and Mathematical Literacy on students' mathematical communication skills.Method: This research is a quantitative study that examines the mathematical communication skills of students by applying the argument driven inquiry learning model and mathematical literacy. The subjects of this study consisted of 30 students learning using the Argument Driven Inquiry model and 30 students using the conventional model. Data were collected through tests and analyzed using One-way Ancova.Results: The findings showed a significant effect of using Argument Driven Inquiry and Mathematical Literacy learning model on students' mathematical communication skills compared to using Conventional learning model. The experimental class obtained higher scores than the control class. Learners were able to organize mathematical arguments more systematically, formulate relevant questions, and convey mathematical thinking more clearly.Conclusion: Argument Driven Inquiry model and mathematical literacy together can affect the mathematical communication skills of students. These results have important implications in the development of mathematics curriculum that pays attention to communication aspects in mathematics learning.